Influence of contextual factors in the adoption of models of unsustainable agriculture. The adoption of the greenhouse in farmers in the horticultural belt of La Plata - Blandi, María Luz; Rigotto, Raquel María; Sarandón, Santiago Javier (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
In recent decades, in the Horticultural Platense Region, much of the open field horticultural farming has been replaced by greenhouse cultivation systems. Even though this practice is more profitable than open field farming, it has a more accentuated negative impact on the ecological and social dimensions of sustainability. The decision-making process of farmers is complex and it’s subject to individual and contextual factors (economic, technical, political and social). The influence of contextual factors in the adoption of greenhouse technology in different Horticultural Platense farmers was analyzed. A qualitative methodology was used, with in-depth interviews with farmers of different origin, who work with various production systems. The results confirm that contextual factors exerted great pressure on farmers when it came to incorporating unsustainable technological innovations. Additionally, it was observed that farmers who practiced greenhouse farming were more influenced by contextual factors than those who practiced open field farming. With a mostly absent State, a weak science and the lack of monetary valuation of environmental assets, the economic dimension prevails when it comes to adopting unsustainable systems.